Development of green coatings with mineral modifiers and natural fillers - Bay, Zehra Meryem; Sahin, Fatma Irem; Acarali, Nil (SAPIENZA UNIV EDITRICE, 2025)
This study presented the improvement of the qualities of organic coatings compounds in construction industry. Different amount ratios, 0-2% (w/w), of red rose petals, hazelnut shells, zinc borate, and thyme oil were added into the water-based interior organic coating. The Box-Behnken optimization technique was utilized to examine the optimum additive-containing composition of organic coatings for better qualities, using coating thickness as response for all experimental sets. R2 value of the equation as 0.9555 between 0 and 1 proved that the experimental data provided a perfect linear curve. The improvement of optimum coating rheological properties was investigated by physical tests; water absorption, impact resistance, covering ability, adhesion, and corrosion. According to Scanning electron microscopy (SEM), a homogeneous and well-dispersed organic coating mixture was obtained. Moreover, it was observed that thermal degradation value for both reference and optimum organic coating compound was protected as 403.15 degrees C by Thermal Gravimetric/Differential Thermal Analysis (TG-DTA) results.
Keywords: Box-Behnken; thyme oil; hazelnut shell; red rose petal; CORROSION PERFORMANCE; ZINC; Geochemistry & Geophysics; Mineralogy